Serological response to a third dose of SARS-CoV-2 vaccine according to previous infection history. (April 2023) - Ota, Kenji; Murakami, Satoshi; Ishihara, Kaori; Sasaki, Daisuke; Usui, Tetsuya; Mitsumoto-Kaseida, Fujiko; Sakamoto, Kei; Kosai, Kosuke; Hasegawa, Hiroo; Takazono, Takahiro; Furumoto, Akitsugu; Asoh, Norichika; et al.
Highlights: Antibody responses induced by SARS-CoV-2 vaccines are influenced by many host factors. Individuals with and without PI benefit from receiving a third dose of vaccine. Higher IgG RBD titers were sustained for longer in the PI group after two doses of vaccine. Abstract: The IgG antibody titer against SARS-CoV-2 receptor binding protein (RBD) after mRNA vaccine were compared between those with and without previous infection (PI) for up to 48 weeks. Though sustained higher IgG-RBD were observed in the PI group after two doses of vaccines, both groups benefited from the booster shots of the third vaccine. This data supports the necessity of the booster shots to those with PI.